Gambaran Tingkat Pengetahuan Ibu Nifas Tentang Pencegahan Infeksi Luka Perineum Di Klinik Kristina Sidikalang Tahun 2021 - Ermawaty Arisandi Siallagan; Febiola Elfrida Manurung (JINTAN: Jurnal Ilmu Keperawatan, 2021)
Background:Rupture is an injury to the perineum caused by natural tissue damage due to pressure on the fetal head or shoulders during delivery. Postpartum infection (puerpuralis) is an infection of the genitalia after childbirth, which is characterized by an increase in temperature to 38ºC or more for 2 days in the first 10 days after delivery, excluding the first 24 hours. Postpartum infection includes all inflammation caused by entry of germs. or bacteria into the genital tract at the time of delivery and postpartum. Objective:The specific purpose of this study was to describe the level of knowledge of the mother about the prevention of perineal wound infection at the Kristina Clinic in 2021. This study used Non Probability Technique Sampling which is the total sampling method. The samples in this study were all postpartum mothers, both those who experienced rupture and those who did not at Kristina Clinic 2021, as many as 20 people. The research was conducted by distributing questionnaires to all postpartum mothers. The results: obtained based on the knowledge of postpartum mothers about the prevention of perineal wound infection based on education, it can be seen from the majority of respondents having good knowledge with 11 people (55.0%) and the minority having knowledge less with the number of 7 people (35.0%). Conclusion: It is hoped that midwives will be able to conduct postnatal visits for 6 weeks in order to monitor the healing process of perineal wounds in patients to avoid infection of perineal wounds and provide education on how to prevent perineal wound infections and the signs and dangers of perineal wounds.